Review paperKeloids and hypertrophic scars - Broniarczyk-Dyła, Grażyna; Wawrzycka-Kaflik, Anna; Urysiak, Izabela (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Keloids and hypertrophic scars are important problems in esthetic dermatology but also in dermatosurgery. Abnormal scarring may cause psychological problems. Keloidal scars and hypertrophic scars are fibrous growths that result from an abnormal connective tissue response in certain predisposed individuals. They are connected with excessive amounts of collagen over prolonged periods. The negro race form keloids more often than other races. The mechanisms underlying the pathogenesis of these abnormal wound responses have not been fully characterized. Trauma, infections, dermabrasion, tattoo, scarring ackne, vaccinations have all been proposed as precipitating factors. Keloids and hypertrophic scars are found most commonly on the midchest, back or shoulders, in places with higher tissue tension. Available methods of treatment include surgical treatment, pharmacological treatment (intralesional steroid injections, external superficial therapy and systemic chemotherapy) and physical treatment. The last of them includes: cryotherapy, laser therapy, pressure therapy and radiotherapy. Any of these could be used alone, but better effects are achieved in combination with other form of treatment. However, the lesions, especially keloids are notoriously recurrent. More effective type of treatments keloids and hypertrophic scars need better understanding of their mechanisms.